Systematic Echocardiographic Evaluation of Mitral Valve Regurgitation for Transcatheter Edge‐to‐Edge Repair. Issue 7 (27th June 2016) - Wallenborn, Julia; Herrmann, Sebastian; Hansen, Marc; Hu, Kai; Voelker, Wolfram; Störk, Stefan; Ertl, Georg; Weidemann, Frank
Abstract : In patients with relevant mitral regurgitation (MR), transcatheter edge‐to‐edge repair (also called MitraClip) provides an alternative treatment option especially for inoperable or high‐risk patients. In preparation for the procedure, echocardiography is the method of choice for assessment of mitral valve (MV) morphology and function and thus provides important information if successful treatment of MR can be accomplished by MitraClip. This review article provides structured and detailed guidance how to systematically assess functional and degenerative MR and MV pathology by echocardiography in order to select eligible patients for this procedure. Furthermore, it highlights state‐of‐the‐art echocardiographic methods and potential pitfalls in patient selection.